Stabilization of recombinant spider silk in thermo-oxidative degradation: High-throughput screening for antioxidants. (July 2018) - Dao, Anh T.N.; Shimokata, Jun'ichi; Takeuchi, Kengo; Nakayama, Koyuru; Taniike, Toshiaki
Abstract: Recombinant spider silk has arisen as one of the most promising nature-derived building blocks owing to its extraordinary mechanical properties, while its instability against thermo-oxidative degradation becomes a major drawback toward industrial applications. Here, we have firstly implemented a high-throughput screening of antioxidants on the stabilization of recombinant spider silk at an elevated temperature. The usage of high-throughput chemiluminescence imaging has allowed us to screen antioxidants with a wide spectrum of molecular structures and quickly provided two good candidates to stabilize recombinant spider silk powder through an impregnation process: E310 and BHT. An accelerated aging has further proven that these antioxidants suppressed the thermo-oxidation of recombinant spider silk through scavenging the formed radical species and slowed down the formation of carbonyl groups as oxidation products. In addition, we have employed a solution mixing process to further improve the stabilization efficacy of the antioxidants and this method also extended our selection on effective antioxidants, including vitamin E, AO-30, AO-40, HP-10, and especially Irganox 1098. These screening results provide guidelines of selecting or even developing potential antioxidants for stabilizing protein materials. Graphical abstract: Image 1 Highlights: Screening of antioxidants was carried out for recombinant spider silk to suppress the thermo-oxidative degradation. Impregnation and solution mixing processes were developed to incorporate antioxidants into recombinant spider silk. Effective antioxidants were quickly found among wide spectrum of molecular structures owing to HTP-CLI. The results provide guidelines of selecting or even developing potential antioxidants for stabilizing protein materials.